The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1080/15548627.2015.1034404
|View full text |Cite|
|
Sign up to set email alerts
|

Divergent roles of BECN1 in LC3 lipidation and autophagosomal function

Abstract: These authors contributed equally to this work.Keywords: autophagy, autophagosome, BECN1, LC3, PtdIns3KAbbreviations: ATG, autophagy related; BafA1, bafilomycin A 1 ; BCL2L1/Bcl -xL, BCL2-like 1; BECN1, Beclin 1, autophagy related; BECN1P1/BECN2, Beclin 1, autophagy related, pseudogene 1; EM, electron microscopy; GAPDH, glyceraldehyde-3-phosphate dehydrogenase; GFP, green fluorescent protein; KO, knockout; MAP1LC3/LC3, microtubule-associated protein 1 light chain 3; MAP1LC3-I/LC3-I, soluble, proteolytically pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 47 publications
4
49
1
Order By: Relevance
“…Our data thus suggest that functional autophagy remain intact when beclin 1 was deleted while DNA DSB repair is dependent on Beclin 1. These results are in contrast to the results of a recent study that reported that deletion of beclin 1 using TALEN disrupted autophagic flux by disrupting the formation of autophagosomes but not by disrupting LC3b lipidation in human Hela cells33. However, the present data appear to be consistent with our recent finding that somatic cells, but not stem cells, can acquire an alternative form of autophagy when their canonical autophagy pathway is disrupted3435.…”
Section: Resultssupporting
confidence: 57%
“…Our data thus suggest that functional autophagy remain intact when beclin 1 was deleted while DNA DSB repair is dependent on Beclin 1. These results are in contrast to the results of a recent study that reported that deletion of beclin 1 using TALEN disrupted autophagic flux by disrupting the formation of autophagosomes but not by disrupting LC3b lipidation in human Hela cells33. However, the present data appear to be consistent with our recent finding that somatic cells, but not stem cells, can acquire an alternative form of autophagy when their canonical autophagy pathway is disrupted3435.…”
Section: Resultssupporting
confidence: 57%
“…We confirmed the attenuation of starvation-induced autophagic activity by showing the reduction in LC3 puncta formation and LC3-II levels (S3D, S3E and S3F Fig) in Beclin 1 KO cells. These results were not inconsistent with that of a previous study [30]. …”
Section: Resultssupporting
confidence: 78%
“…LC3 appears as LC3-I and LC3-II in the cytoplasm, but LC3-I is converted to LC3-II when autophagy occurs. LC3-II is the significant protein of autophagosome which is considered as the molecular marker of autophagosome, so the ratio of LC3-II/ LC3-I was employed to reflect the degree of cell autophagy [15]. Our findings showed that the ratio of LC3-II/LC3-I in MG63 cell was remarkably lower than that in osteoblast, revealing the lower autophagy activity of MG63 cells compared with normal cells.…”
Section: Discussioncontrasting
confidence: 49%